Faktor-Faktor yang Mempengaruhi Behavior Intention Masyarakat Gen Y dalam Menggunakan QRIS pada Berbagai Toko Ritel di Kota Batam - Kharisma Austin Makaba (Yayasan Literasi Sains Indonesia, 2023)
Despite the previous severe contraction, the economy has gradually recovered, as evidenced by the resumption of significant transactions. One visible thing is the development of digitization in terms of converting conventional transactions into digital transactions such as the use of QRIS (Quick Response Code Indonesia Standard). In Batam City, it was reported by BI Kepri that the number of QRIS merchants increased by 10.28% from the first quarter of 2022, and users increased by 92.65% from the first quarter to 117,686 (y-o-y). However, many people have not switched to digital payments like Gen Y. The KIC survey spread across 34 provinces found that more Gen Y use conventional bank accounts than digital wallets and the use of digital wallets is dominated by Gen Z of 68%. This research aimed to analyze the factors that influence the Behavior intention of the Gen Y community in using QRIS in various retail stores in Batam city. The sample in this research was 101 respondents who were chosen according to predetermined criteria. The research model used a combination of TAM and TPB, with multiple linear regression analysis using SPSS. The results showed that Perceived Ease to Use had a significant effect on Perceived Usefulness, then Perceived Usefulness & Perceived Ease to Use affected Attitude, as well as the PEU, PE, Attitude, & Perceived Behavior control variables had a significant effect on behavior intention while the Subjective Norms variable did not significantly effect on behavior intention.